Efeito da adubação nitrogenada e de seu parcelamento sobre a cultura do milho, em Patos de Minas - Viana de Novais, Moacyr; Ferreira de Novais, Roberto; Braga, José Mário (Revista Ceres, 2025)
A field trial was conducted at Patos de Minas to study the effect of three nitrogen levels (0,60 and 120 kg/ha) applied at different times during the growing season on total ear production, percentage of rejected ears, mean weight cóf-.ears and foliar levels of nitrogen, phosphorus, potassium, calcium, and magnesium. A corn hybrid obtained from Agroceres, a Brasilian seed production company, was used in this experiment.